Hubungan Alokasi Waktu Kerja terhadap Kondisi Ekonomi Petani Rawa Lebak di Pulau Kemaro - Yamin, Muhammad; Arbi, Muhammad; Januarti, Indri; Sari, Yeka Puspita; Putri Pramalia, Regita (Seminar Nasional Lahan Suboptimal, 2022)
Yamin M, Arbi M, Januarti I, Sari YP, Pramalia RP. 2022. The relationship between work time allocation and economic conditions of the swamp land farmers on Kemaro Island. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang  27 Oktober 2022. pp. 243-253.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The level of soil fertility and agricultural infrastructure in swam is relatively lower than the irrigated paddy fields. So that the allocation of working time greatly affects the success of the farming business. The purpose of this study was to analyze the relationship between the allocation of working time and the economic conditions of farmers on Kemaro Island, Palembang City. This study has used a survey method with simple random sampling. The number of samples that have been taken is 44 respondents or 55% of the population. The results of this study showed that the total allocation of working time for farmer families was 367.12 HOK / year. In detail, the allocation for agriculture is 56.06 HOK/year and 311.06 HOK/year allocation for non-agricultural. The socioeconomic condition of farming families is relatively low, as evidenced by the fact that 36% of farming families are below the poverty line and the rest are close to poor.  There is a significant relationship between the allocation of working time and the economic conditions of the farming family. It can be concluded that the condition of farmers on tidal lands with a low level of soil fertility, infrastructure and technology, the allocation of working time is an important factor for improving the socioeconomic conditions of farmer families. There is a significant relationship between the allocation of working time and the income of farmer’s family.